PENGARUH KREATIVITAS PEMBINA SEKAMI TERHADAP MINAT ANAK UNTUK MENGIKUTI PEMBINAAN SEKAMI DI PAROKI MARIA BUNDA SELALU MENOLONG KAMBAJAWA - Manao, Rosalia Melani; Taek, Emilia Dolorosa; Dau, Yoseph L. D.; Bele, Graciana Amanda (STIPAS Keuskupan Agung Kupang, 2024)
This study aims to determine the extent to which the creativity of SEKAMI coaches affects children's interest in attending SEKAMI coaching at Maria Bunda Selalu Menolong Kambajawa Parish. The research method used is quantitative research with a descriptive correlational approach. Data collection techniques used questionnaires and documentation studies. The questionnaire was addressed to 214 SEKAMI coaches and children, to find data on the level of creativity of SEKAMI coaches and the level of children's interest in joining SEKAMI coaching. The data analysis technique used was descriptive and inferential statistical analysis. As a result of the research, the average of each indicator of the SEKAMI coach's creativity variable (X) was 80.98% and the average achievement of each indicator of the child interest variable was 71.13% and the child's interest in participating in SEKAMI coaching was in the good category. In addition, in the calculation of the coefficient of determination (R2), SEKAMI coach creativity (X) has a contribution of 81.7% to children's interest (Y) (0.817 x 100 = 81.7%). Based on the t-test, 6.678 is greater than the t table value of 1.971. Therefore, the hypothesis in this study is accepted and there is a positive and significant influence of SEKAMI coaches' creativity on children's interest in joining SEKAMI coaching at Maria Bunda Selalu Menolong Kambajawa Parish.